2018
DOI: 10.1002/jsp2.1017
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of high‐quality RNA from intervertebral disc tissue via pronase predigestion and tissue pulverization

Abstract: The isolation of high‐quality RNA from the intervertebral disc and especially from the nucleus pulposus is challenging due to the low cellularity and high proteoglycan content of this tissue. In this study, we report a simple modification of the standard guanidinium thiocyanate‐phenol‐chloroform extraction method, which involves enzymatic predigestion of the tissue prior to standard RNA isolation. Yield, purity and integrity of RNA isolated from bovine nucleus pulposus, inner annulus fibrosus and outer annulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 25 publications
0
29
0
1
Order By: Relevance
“…Recently, AngII was also demonstrated to have haemodynamic-independent effects, such as contribution to inflammation, hypersensitivity and fibrosis in many organs, including liver, kidney and skin (Kranzhofer et al, 1999;Paul et al, 2006;Ruiz-Ortega et al, 2001). Previous studies have also shown that inflammatory cells expressed RAS components and AngII contributed to axon sprouting and regeneration (Chakrabarty et al, 2008;Hoch et al, 2009). Therefore, the definition of "local" or "tissue" renin-angiotensin system (tRAS) was introduced (Paul et al, 2006).…”
mentioning
confidence: 99%
“…Recently, AngII was also demonstrated to have haemodynamic-independent effects, such as contribution to inflammation, hypersensitivity and fibrosis in many organs, including liver, kidney and skin (Kranzhofer et al, 1999;Paul et al, 2006;Ruiz-Ortega et al, 2001). Previous studies have also shown that inflammatory cells expressed RAS components and AngII contributed to axon sprouting and regeneration (Chakrabarty et al, 2008;Hoch et al, 2009). Therefore, the definition of "local" or "tissue" renin-angiotensin system (tRAS) was introduced (Paul et al, 2006).…”
mentioning
confidence: 99%
“…1). Thus, www.ecmjournal.org they were defined as markers of functional AF cells (Bron et al, 2009;Costi et al, 2007;Nakamichi et al, 2016;Schmidt et al, 2007). Each of these markers had previously been shown to be related to AF tissue function.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these markers had previously been shown to be related to AF tissue function. Collagen type I expression at both gene and protein level is a well-known marker of AF cells in all species related with the tissue ECM property, since the proportion of collagen type I increases from the NP towards the outer AF (Bron et al, 2009). MKX expression at both gene and protein level has recently been identified as a transcription factor for AF cell differentiation, where MKX knock-out mice showed a much smaller collagen fibril diameter and a more rapid IVD degeneration as compared with the wild type mice (Nakamichi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations